2019
DOI: 10.3847/1538-4357/ab0383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Optical Classification of Fermi BCUs Using Machine Learning

Abstract: In the third catalog of active galactic nuclei detected by the Fermi-LAT (3LAC) Clean Sample, there are 402 blazar candidates of uncertain type (BCUs). Due to the limitations of astronomical observation or intrinsic properties, it is difficult to classify blazars using optical spectroscopy. The potential classification of BCUs using machine-learning algorithms is essential. Based on the 3LAC Clean Sample, we collect 1420 Fermi blazars with eight parameters of γ-ray photon spectral index; radio flux; flux densi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 69 publications
1
34
0
Order By: Relevance
“…We then compared our 120 identified BL Lac candidates with some other recent studies. We found that our results are mostly consistent with previous works presented in Chiaro et al (2016); Lefaucheur & Pita (2017); Yi et al (2017) and Kang et al (2019a) which utilize different statistical (e.g., SML) algorithms (see Table 4 and Table 3). The exceptions are as follows: 2 sources do not find matching sources and 2 sources did not provide a clear classification in Lefaucheur & Pita (2017).…”
Section: Comparison With Literature Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We then compared our 120 identified BL Lac candidates with some other recent studies. We found that our results are mostly consistent with previous works presented in Chiaro et al (2016); Lefaucheur & Pita (2017); Yi et al (2017) and Kang et al (2019a) which utilize different statistical (e.g., SML) algorithms (see Table 4 and Table 3). The exceptions are as follows: 2 sources do not find matching sources and 2 sources did not provide a clear classification in Lefaucheur & Pita (2017).…”
Section: Comparison With Literature Resultssupporting
confidence: 91%
“…The exceptions are as follows: 2 sources do not find matching sources and 2 sources did not provide a clear classification in Lefaucheur & Pita (2017). In addition, only 3 sources are classified as FSRQs in M clust Gaussian Mixture Modelling (M 8 ), and two are classified as FRSQs using support vector machine (SVM 8 ) using 8 parameters in Kang et al 2019a; 1 source is classified as an FSRQ in Chiaro et al 2016 (Chi16), whereas two sources are classified as FRSQs in Yi et al 2017 (Y17). The results, provided in Table 4, indicate the highest mismatch rate (e.g., rate = 3/120% ∼2.5%) is less than 3%.…”
Section: Comparison With Literature Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we also should note that all of the default settings (e.g., the probabilities: p > 0.5 in each classifier to consider a correct classification, see Table 3) for each of the three classification functions (e.g., randomF orest(), svm() and nnet() function) are used in Section 4. For each different classification method, choosing the calculation model and setting each parameter in the fitting function can also affect the predictive models, accuracy, and results (e.g., see the discussions in Kang et al 2019). The selections of the appropriate parameter settings need further investigation; this is beyond the scope of the current work.…”
Section: Discussionmentioning
confidence: 99%
“…Duev et al () trained a CNN to discover fast‐moving candidates from ZTF observations in order to more reliably identify potentially hazardous near‐Earth objects. Active galactic nuclei and quasars . A common theme in this field is the need for classification and detection methods, including assigning morphological types to radio‐detected active galactic nuclei with a CNN (Ma et al, ), identifying blazar candidates in the Fermi‐LAT (3LAC) Clean Sample (Kang et al, ), detecting rare high‐redshift, extremely luminous quasars (Schindler et al, ), and discriminating populations of broad absorption line quasars (BALQs) from non‐BALQs in SDSS data releases (Yong et al, ). Cosmological simulations . ML is providing new methods for examining the outputs of cosmological simulations, leading to new insights about the connections between physical properties of galaxies, dark matter halos and the cosmic environment.…”
Section: Assessing the Maturity Of Adoptionmentioning
confidence: 99%